France : Report on the Observance of Standards and Codes-Monetary and Financial Policies Transparency and Fiscal Transparency-Updates. (IMF Staff Country Reports; Country Report, 2002)
This report evaluates the Observance of Standards and Codes on Monetary and Financial Policies Transparency and Fiscal Transparency for France. Up to mid-2001, different rules were applied to insurance firms regulated by the Insurance Code and to establishments regulated by the Code de la Mutualite. Moving toward the consolidation of these rules, a new Code de la Mutualite was ratified by Parliament in July 2001. Now, prudential rules concerning authorizations for new entrants in the insurance business, technical provision, and solvency margins are the same for all companies in the sector.